IMPACT OF COVID 19 PANDEMIC ON STRUCTURE OF PATIENTS UNDERGOING SURGICAL TREATMENT FOR URO-ONCOLOGICAL INDICATIONS - Skakić, Aleksandar; Ignjatovic, Ivan; Potic, Milan; Dinic, Ljubomir; Pejic, Bratislav; Stamenic, Tomislav; Pejic, Aleksandar; Mihajlovic, Marija; Janic, Jovan; Basic, Dragoslav (Acta medicae Medianae, 2024)
The aim of this retrospective study was to examine the impact of the COVID-19 pandemic on the structure of patients who had undergone operative treatment for oncological indications at the Urology Clinic of the University Clinical Center Niš in the period from March 2018 to June 2022. The following operations were included: nephrectomy for kidney cancer, nephroureterectomy for upper urothelial cancer, prostatectomy for prostate cancer, cystectomy for bladder cancer, orchiectomy for testicular cancer and penectomy for penile cancer. Data were taken on the number of operations, patients’ age and gender and postoperative histopathological findings. Depending on the time the surgery was performed, patients were divided into two groups: the preCOVID group - procedures carried out before the start of the pandemic (March 1, 2018 − March 1, 2020) and the COVID group - procedures carried out after the start of the pandemic (June 2020 − June 2022). A total of 569 investigated operations were performed, 320 before and 249 after the beginning of the pandemic. Nephrectomies were the most frequently performed procedures in both study groups. During the pandemic, a significant decrease in number of prostatectomies and nephrectomies was registered. The proportion of prostatectomies was significantly lower in the COVID group, while the proportion of cystectomies significantly increased. The frequency of stage T4 bladder cancer was significantly higher during the pandemic, while the frequency of stage T3a was significantly lower. When we consider the results of tumor stages after all operative procedures in our study, significantly more patients with T4 stage were registered during the pandemic, the majority with bladder cancer.